PENGEMBANGAN INSTRUMEN PENILAIAN KINERJA PRAKTIKUM SUHU DAN KALOR KELAS X SMA - Ihsany, Zaimul (Jurnal Evaluasi Pendidikan, 2017)
The purpose of this study is to develop a practical performance assessment instrument of temperature and heat material in class X of Senior High School. The samples were taken by using stratified random sampling method. Conceptually, the construct of performance assessments of temperature and heat the material consists of three dimensions, namely: preparation, implementation, and follow-up. Development of point statement on assessment component is based on the study of experts and panelists. Through study and validation, expert panelists choses 10 points or indicators. Reliability coefficients interater value is quite high above 0.7. Instruments were tested students at SMA in class X, the first stage are 256 students and the second stage are 224 students. Empirically, by testing confirmatory factor analysis is obtained the values of loading factor is abave 0.5 in the first and second trials. From the calculation of the value of Construct Reliability (CR) on the first and second test showed that reliability coefficient value is more than 0.9, and the value of Variance Extracted (VE) is greater than 0.5 which means the level of validity and reliability of a practical performance assessment instruments of temperature and heat materials in class X SMA is high. So it can be concluded that the practicum performance assessment instrument temperature and heat the material has good validity and reliability construct.